Role Of Reliable Policies In Promoting Research And Knowledge Management: The African Context - Joseph, Bwalya Kelvin (Journal of Knowledge Management Practice, 2009)
Many countries the world over have appreciated the role of research and Knowledge Management (KM) in their socio-economical development. African governments, just like any others all over the world, have a duty to incorporate into their public policies and knowledge-related activities the UN’s Millennium Declaration as a framework for knowledge society. This paper presents an ad hoc survey looking at endeavours done towards establishing research as a public good in Botswana, Zambia and Malawi. It brings out lessons learnt on how research can or cannot contribute to national development, and further establishes the niche of research and effective knowledge management as a tool toward shaping a nation on the competitive edge in the global value chain. Incorporation of the research and knowledge management agenda into national policies is not an easy thing to do, as a lot of challenges are evident from case studies where this has been tried.